Analisis Faktor-Faktor yang Mempengaruhi Keputusan Perempuan Menjadi Pekerja Migran dalam Upaya Peningkatan Kesejahteraan Keluarga di Kecamatan Utan Kabupaten Sumbawa Besar - Iyan Ardiansyah; Fitria Permata Cita (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
The purpose of this study is to examine the influence of income and employment opportunities on women's decision to become migrant workers, as well as the impact on the level of family welfare of women migrant workers. The approach used is a quantitative method by utilizing primary data collected through the distribution of questionnaires to female respondents who have worked or are currently working as migrant workers in Kecamatan Utan, Kabupaten Sumbawa Besar. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the help of SmartPLS software. The research variables were measured using a number of indicators formulated based on the theoretical basis and the results of previous studies. The findings show that income has a positive and significant influence on women's decision to work as migrant workers, with a coefficient of 1.940 and a p-value of 0.000. In contrast, employment opportunities have a negative and significant effect on the decision, with a coefficient of -1.147 and a p-value of 0.000. Furthermore, women's decision to become migrant workers has a positive and significant effect on family welfare, as shown by a coefficient of 0.594 and a p-value of 0.001. However, income does not have a significant direct effect on family welfare, with a p-value of 0.151. Meanwhile, employment opportunities have a positive and significant influence on family welfare, with a coefficient of 0.691 and a p-value of 0.030. These results indicate that women's decision to become migrant workers functions as a mediating variable in efforts to improve family welfare.